Rights human on international level (Journal of actual problems of jurisprudence, 2018)
The aim of the work is to address human rights issues arising in connection with the preparation of a complex system. The methodological basis of the work related to the protection of human rights at the international level, both foreign and domestic science research. During the study, the analysis of the system, reputation and other scientific methods. Experience in the application of international human rights law. One aspect of the problems related to human rights on the international level – how to use them. Key words: International organization of right, right human to protect.